Laboratory Evaluation of IPS-lithium Disilicate Orthodontic Brackets (In vitro Study) - Sana R. Ubaed; Omer S. Ali (Polytechnic)
The purpose of the study is to evaluate the microhardness and light transmission through new Emax brackets with two ceramic brackets commercially available in the markets. The brackets were divided into three groups: (1) E max brackets (IPS E-max press, Ivoclar, Germany), (2) Gemini clear brackets (Unitek, 3M, USA), and (3) discovery pearl ceramic brackets (Dentaurum, Germany). The Vickers hardness test was used to evaluate the hardness of the wings in addition the light transmission of three brackets types were tested through using an orthodontic light cure device and light meter. The hardness test of discovery pearl ceramic brackets and Gemini clear brackets gave significantly higher than E.max one while later gave significantly more light transmission through it when compared with another two brackets. In conclusion, the noticeable tested brackets make E max material one of choice for modern esthetic brackets in future although the hardness is less comparing the other tested brackets due to the purity of material compering with other test brackets which are reinforced of their material, the new material requiring improving of mechanical performances.